KOMPOSISI JENIS DAN STRUKTUR VEGETASI HUTAN DI KAWASAN SUAKA MARGASATWA CIKEPUH, SUKABUMI – JAWA BARAT - Polosakan, Ruddy (Jurnal Teknologi Lingkungan, 2010)
A study on the structure and composition of trees species was carried out in Cikepuh Game Reserve. The informations and data on forest ecosystems of Cikepuh Game Reserve was still very limited. Method of study used point centered quarter. The results of study recorded total species number was 55 species of trees consisted of 35 genera and 26 families, while saplings (Belta) recorded was 51 species consisted of 34 genera and 23 families.The common species of trees in the area were Vitex pinnata (Important Value = 53.37%), Alseodaphne cunneata (IV = 44.12%), Aporosa microcalyx (IV =25.88%) and Helicia robusta (IV = 24.38% ), while saplings were Vitex pinnata (IV =27.82%), Dillenia aurea (IV = 27.11%), Microcos tomentosa (IV = 25.72%), Aporosa microcalyx (IV = 23.10%) and Phyllanthus emblica (IV = 21.62%).Key words : structure, composition, trees species, Cikepuh Game Reserve